ANALISIS KONTRIBUSI DANA BAGI HASIL SUMBER DAYA ALAM DALAM BANTUAN PEMBIAYAAN BELANJA PROVINSI KALIMANTAN TIMUR PERIODE 2012-2021 - Lestari, Afifah Dini; Ellyawati, Noor; Rahayu, Vitria Puri (Educational Studies: Conference Series, 2023)
The condition of revenue sharing funds from natural resources in East Kalimantan Province shows fluctuating conditions tending to decline, profit sharing funds contribute positively to the regional financial assistance budget which is useful for regional progress and development. The aim of this research is to determine the magnitude of the contribution of natural resource revenue sharing funds to financial aid spending, as well as determine the largest contribution from both renewable and non-renewable natural resources. This research is a type of qualitative research with data collection techniques using documentation and data analysis using the fiscal decentralization formula. The results of the research show that every year the contribution of the Profit Sharing Fund contributes to the financial aid expenditure of the province of East Kalimantan, this is because the amount of the profit sharing fund tends to decrease every year while the budget for aid expenditure for the province of East Kalimantan continues to increase.